2006
DOI: 10.1093/ndt/gfl237
|View full text |Cite
|
Sign up to set email alerts
|

Paulista registry of glomerulonephritis: 5-year data report

Abstract: Focal segmental glomerulosclerosis was the most frequent primary glomerular disease, followed by membranous nephropathy and IgA nephropathy. Lupus nephritis predominated over all the other secondary glomerular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
83
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(119 citation statements)
references
References 21 publications
19
83
2
1
Order By: Relevance
“…Clinicopathological correlations observed in our study are shown in Table 3 proliferative GN and segmental proliferative GN [5,14]. Our classification is most similar to Italian [2,3], Spanish [6,7] and Czech [8] report, with some minor differences.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Clinicopathological correlations observed in our study are shown in Table 3 proliferative GN and segmental proliferative GN [5,14]. Our classification is most similar to Italian [2,3], Spanish [6,7] and Czech [8] report, with some minor differences.…”
Section: Resultssupporting
confidence: 82%
“…The most common indication for renal biopsy in our patients was NS in total (40.3%) and also in men (42.6%), while in women it was AUA (38.8%). In most registry and database reports, NS was also the most common indication [6,8,14,18,19,25], while in Italy [2] and in Belgium [20] it was AUA. As we stated earlier, this depends on the biopsy policy of different country or region, but also on availability of the biopsy and socio-economic status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several authors, the worldwide incidence of FSGS is on the rise annually, including in Brazilian statistics (1,8,9) . Data from the Paulista registry of glomerulopathies shows that FSGS is the most common primary glomerulopathy in 11 centers of São Paulo, accounting for 29.7% of cases, followed by membranous nephropathy (20.7%) and immunoglobulin A (IgA) nephropathy (17.8%) (12) . From an etiological standpoint, FSGS may be associated with a variety of conditions, including viral infections (human immunodeficiency virus [HIV], simian virus 40 [SV40] , parvovirus B19), several drugs (heroin, pamidronate, interferon), adaptive to hyperfiltration (as in hypertension, obesity, and sickle-cell anemia), and genetic disorders (familiar forms), and may be idiopathic (11) .…”
Section: Introductionmentioning
confidence: 99%
“…4 In Brazil, the Paulista Registry of Glomerulopathies has reported that the frequency of biopsies in patients over the age of 60 years accounts for 8.0% of the notified cases, and, in those over the age of 80 years, for 0.4%. 5 Another Brazilian study has reported that 2.2% of the 9,617 biopsies in native kidneys were performed in elderly patients. 6 This study aimed at assessing the distribution, clinical characteristics, and evolution of the nephropathies diagnosed by use of renal biopsy in the elderly.…”
Section: Introductionmentioning
confidence: 99%